Community resilience to power outages after disaster: A case study of the 2010 Chile earthquake and tsunami. (March 2019) - Moreno, Jenny; Shaw, Duncan
Abstract: This paper examines the short and long-term societal impact of prolonged power outages caused by a disaster, and the way of coping that the community develops. Community resilience is used as a conceptual framework to analyse the community responses to power outages following the 2010 Chile earthquake. Based on empirical evidence from longitudinal qualitative research we explore the resilience capacities and resources deployed in five low-income communities within Talcahuano, one of the cities most heavily affected by the power outage. Our research reveals that community resilience attenuates the negative consequences of power outages during the response and recovery periods. However, external assistance is required to reduce the short and long-term societal impact of prolonged outages. Policy recommendations and guidelines are provided on how to increase community resilience and reduce the negative impact of long-lasting power outages. Highlights: We analysed seven years of societal impact derived from a prolonged power outage following a disaster. Community resilience attenuated the negative consequences of power outages. Communities deployed collective actions to cope with prolonged outages caused by disasters. External assistance is required to reduce the societal impact of power outages.